La prognosi dei distacchi epifisari dell’arto inferiore - Gigante, C.; Corradin, M.; Gorgoglini, G.; Maglione, P.; Ippolito, E. (Lo Scalpello - Journal, 2018)
THE PROGNOSIS OF FRACTURE SEPARATIONS OF THE LOWER LIMBS Physeal fractures, which represent almost 25% of all the fractures in children, are generally classified according to the Salter Harris (S-H) classification, which is accepted worldwide thanks to its simplicity and reproducibility. However, during the last two decades several reports have questioned its prognostic value. In this review, the main prognostic factors of lower limb physeal injuries were identified on the basis of our personal experience and of the most recent literature. Although a bad prognosis may be still recognised as S-H type III and type IV, particularly when anatomic reduction of the articular fracture is not obtained, type I and type II lesions may also have a poor outcome especially in case of high-energy trauma.